3-DIMENSIONAL MODELING OF THE ARCHIPELAGO FISHERY HARBOR PIER SIBOLGA USING SAP2000 - Syere Novia Giovanny; Arthur Brown; Ronald Mangasi Hutauruk (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
ABSTRACTThis research was conducted on April 29th until May 13th 2019 at the Sibolga Archipelago Fisheries Port. The method used is a survey method. The purpose of this study was to determine the shear forces and force moments experienced by the 3D model of the Sibolga Archipelago Fishery Harbor wharf when it was loaded using the SAP2000 application. From the value of the shear force and moment of force, the average pile structure condition is damaged or broken (colored red). Broken piles caused by workloads given to the model of the structure of the pier building, giving workloads resulted in the pier model experiencing shear force and moment of force, the largest load given is the nominal base shear load due to earthquake on the x and y axis. Using SAP2000 application there are two colors on the pile namely blue and red, blue indicates the structure is very strong while the red color shows broken structures. So we get the conclusion that the pile has a limit to the shear force (P, V2, V3) and moment of force (T, M2, M3).Keywords: Jetty, Modeling, Loading, SAP2000